Perlindungan Hukum Terhadap Pihak Pemberi Pinjaman Akibat Terjadinya Gagal Bayar pada Peer to Peer Lending - Dewanthara, Ni Made Intan Pranita; Subha Karma Resen, Made Gde (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 5 No 3 (2020)DO - 10.24843/AC.2020.v05.i03.p04, 2020)
The digital world has developed very rapidly and has had a lot of influence in various sectors, one of which is the presence of information technology-based lending and borrowing services, namely Peer to Peer Lending. However, it is possible that the implementation of Peer to Peer Lending carries a risk of a legal problem, namely the default from the Loan Recipient which will harm the Lender who funds the loan application on the Operator's platform. In this regard, the next study aims to identify and analyze legal protection for lenders related to the risk of default in peer to peer lending based lending services. In addition, this study also aims to explain dispute resolution due to default in peer to peer lending. The research method used in this research is normative legal research method. Legal protection for lenders with the formation of special regulations that provide protection for Peer to Peer Lending service users, namely the Financial Services Authority Regulation Number 77 / POJK.01 / 2016 in particular Article 37 and sanctions such as fines, imprisonment, and other additional penalties given after it occurs dispute. Settlement of disputes due to default in P2PL can be carried out outside or inside the court in accordance with Article 39 paragraph (1) POJK Number 1/POJK.07 / 2013.